Community Economic Empowerment Using Urban Farming in Pontianak - Maswadi Maswadi; Novira Kusrini; Shenny Oktoriana; Anita Suharyani (Universitas Sebelas Maret, 2025)
Urban farming has emerged as a viable strategy to address limited land availability, food insecurity, and economic vulnerability in urban areas. In Southeast Pontianak District, West Kalimantan, high population density and limited green space pose significant barriers to community-based agricultural initiatives. This community service initiative aims to enhance the community's understanding of how to manage agricultural practices in small-scale areas. This program empowered 48 local residents, especially housewives and unemployed youth, through participatory training in hydroponics and verticulture techniques. The program utilized workshops, counseling sessions, and hands-on practice in household waste recycling for plant cultivation and fertilizer production. Post-training evaluation revealed impressive implementation rates, with 77.1% of participants (n=37) actively practicing urban farming within three months. Among implementers, adoption patterns demonstrated program flexibility: 40.5% adopted hydroponics exclusively, 21.6% focused on verticulture, while 37.8% integrated both techniques. Cultivation diversity was substantial, with 48.7% growing 1-3 plant varieties and 37.8% managing 4-6 species. Timeline analysis showed 62.2% began implementation within 1-3 months, while 37.8% sustained practices for 4-6 months, indicating long-term behavioral change. Results demonstrate increased community awareness, technical capacity, and sustainable practice adoption. The high implementation rates and diverse patterns suggest program success in creating adaptable solutions for varied household conditions, with strong potential for scalability to similar urban contexts.